The Effect of Capital Intensity, Profitability, and Leverage on Tax Avoidance in Transportation and Logistics Companies Listed on the Indonesian Stock Exchange - khoirunnisa, khoirunnisa; Helmi, Sulaiman; Sartika, Dewi; Gustini, Emilia (International Journal of Finance Research, 2025)
The purpose of this study is to determine the effect of capital intensity, profitability, and leverage on tax avoidance in transportation and logistics companies listed on the Indonesia Stock Exchange. Tax avoidance is a deliberate approach taken by individuals, organizations, or legal entities to reduce their tax liabilities legally. This study uses secondary financial statement data accessible through the Indonesia Stock Exchange website at www.idx.co.id. The population in this study consists of 84 transportation and logistics companies, and the sample used comprises 28 companies. The sampling method used is purposive sampling, with data analysis techniques employing multiple linear regression through the SmartPLS version 4 program. The results of this study indicate that capital intensity influences tax avoidance. Meanwhile, profitability and leverage do not influence tax avoidance